Corrosivity of Pongamia pinnatta biodiesel on zinc and its alloy - a comparison. (2016) - Meenakshi, H.N.; Lakshmi, M.C. Prasanna Venkata; Anand, Anisha; Shyamala, R.; Saratha, R.
Biodiesel has been widely put to use all over the world on account of global warming prevention and reduction of fossil fuel consumption. Oxidation of biodiesel is determined by the degree of unsaturation in the fatty acid alkyl ester chain, water content and environmental factors such as temperature, nature of storage container and air exposure during storage. The corrosivity of biodiesel on metals is higher than diesel due to their distinct chemical characteristics. Some metals have a catalytic effect on the biodiesel oxidation process which causes severe corrosion during long-term storage. Higher concentrations of biodiesels may begin to create problems more rapidly with zinc, tin, brass and bronze. Hence the present study is aimed to investigate the corrosivity of Pongamia pinnata biodiesel (PBD) and its blends with commercial diesel on zinc and brass by mass loss method. Zinc was found to be highly corroded than brass in PBD. The surface morphology and the elemental composition of the corrosion products were determined by scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS). Corrosion products on the PBD exposed metals were also examined by X-ray diffraction (XRD).